Normalisation of menstrual pain: the silent driver of gynaecological diagnostic delays among young girls - Noor, Aliya; Nurie, Iqra Moatter (Journal of the Pakistan Medical Association, 2026)
The pervasive normalisation of dysmenorrhea is a critical public health issue that masks serious gynaecological pathology and leads to significant diagnostic delays. Globally, menstrual pain is frequently dismissed as an inevitable part of womanhood. This normalisation contributes to a diagnostic delay of several years for conditions like endometriosis.1 In Pakistan, socio-cultural taboos exacerbate this problem. Menstruation is shrouded in secrecy and shame, discouraging open discussion and limiting girls' knowledge about their own physiology.2 Studies indicate that the majority of young women manage dysmenorrhea with self-prescribed analgesics or home remedies, with only a small minority seeking professional care.3 When help is sought, symptoms are often minimised by primary healthcare providers, reinforcing a cycle of silence and neglect.4 This collective dismissal has serious consequences. Treating severe pelvic pain as "normal" allows underlying conditions such as endometriosis, adenomyosis, or pelvic inflammatory disease to progress unchecked, potentially affecting future fertility and quality of life.We urge a multi-pronged strategy to address this issue: Integrate comprehensive menstrual health education into national school curricula to foster informed dialogue from a young age. Implement targeted training for primary care providers to improve the recognition of "red flag" symptoms associated with menstrual pain, moving beyond dismissal to proactive investigation. Launch public health campaigns to destigmatise menstruation and encourage timely healthcare-seeking behaviour.Shifting the perception of dysmenorrhea from a normal inconvenience to a potential indicator of pathology is essential. Proactive education, clinical vigilance, and cultural change are imperative to protect the long-term reproductive health of young women in Pakistan.